Routine measurement of serum calcitonin in patients with nodular thyroid disorders? - Dietlein, M.; Wieler, H.; Schmidt, M.; Schwab, R.; Goretzki, P. E.; Schicha, H. (Nuklearmedizin - NuclearMedicine, 2008)
In spite of the fact that the German Society of Endocrinology has recommended calcitonin as screening-parameter the majority of physicians in Germany do not routinely use calcitonin in patients with thyroid nodules to exclude medullary thyroid cancer (MTC). The future revision of the recommendation should describe reference values for each commercially available assay, separately for men and women (basal and after pentagastrin-stimulation), and should define sonomorphological inclusion criteria. The epidemiological database of the prevalence of MTC is controversial and the specificity of basal elevated calcitonin levels is limited up to the 5-fold of the upper reference level. If renal insufficiency, bacterial infection, and an alcohol- or druginduced stimulation of calcitonin is excluded, hypercalcitoninaemia should be confirmed by a second measurement (if necessary using another assay). Stimulation of calcitonin by use of pentagastrin is mandatory prior to the decision on thyroidectomy. A stimulated calcitonin level <100 pg/ ml justifies “wait and see”. If stimulated calcitonin levels range between 100 and 200 pg/ml or higher, the differentiation between C-cell hyperplasia and MTC remains uncertain, especially in men. The implementation of calcitonin- screening requires the definition of sonographic inclusion criteria and validation of each assay. Additional prerequisites are excellent logistic (short period between blood sampling and start of the laboratory test), knowledge of differential diagnoses, knowledge of the consumption of drugs and alcohol, availability of pentagastrin-testing and of moleculargenetic testing with full information to the patients and sufficient time before the decision on surgery is made. All this and the choice of a skilled surgeon, experienced in thyroidectomy and lymphadenectomy with a low rate of local complications are the rationale to recommend calcitonin-screening primarily in centers for thyroid disorders.
Keywords: Calcitonin; screening; thyroid nodule; medullary thyroid cancer; C-cell hyperplasia